Evaluation of Physical Characteristics of Edible film from Bligon Goat Skin Gelatin using Glycerol as Plasticizer - Muhammad Irfan Said; Suharjono Triatmojo; Yuny Erwanto; Achmad Fudholi (Jurnal Ilmu dan Teknologi Hasil Ternak (JITEK), 2013)
The use of glycerol as a plasticizer in the film solution mixture was identified to the physical properties of edible film. The objectives of this study was to evaluate the physical characteristics of edible films using gelatin from Bligon goat skin as a raw material with glycerol as a plasticizer. The experiment was conducted in a laboratory experiment using completely randomized design (CRD) method. There were three concentrations of glycerol as a plasticizer, namely: 80%, 90% and 100% (calculated from the amount of gelatin is 9%). The variables of this study were thickness, tensile strength and elongation et break. The results of this study showed that the difference in the concentration of glycerol as a plasticizer in the gelatin of 9% gave no significant effect on the thickness and tensile strength of edible films, however very significant effect on the elongation et break. It was proven that glycerol concentration of 80% as a plasticizer had been better physically. Â Key words: edible film, gelatin, Bligon goat skin, glycerol, plasticizer